Leadership Team Coaching in Practice : case studies on creating highly effective teams - Hawkins, Peter, 1950- (New York : Kogan Page, 2022)
"A high-performing and cohesive leadership team is essential for organizational success. Leadership Team Coaching in Practice provides an overview of the tools and techniques for coaching leadership teams and shows how these approaches have been applied around the world in a variety of team types and industries. Featuring expert contributions from chief executives, team coaches, team leaders and consultants in organizations including Comair and the UK National Health Service (NHS), this practical guide illustrates best practice tailored to the needs of each organization. The new and updated third edition of Leadership Team Coaching in Practice incorporates the latest research and thinking in the field, including new material on developing the personal core capacities for systemic team coaching. Alongside updates to case studies to offer a long-term view of interventions, the third edition contains new case studies including team Coaching in Toyota through a period of transformation. There is a new medley chapter of short case stories that address some of the regularly asked questions by new team coaches and new material that explores ways of creating a teaming and team of teams culture; This book remains an essential resource for executive and team coaches, CEOs, team leaders, organizational development consultants, and those studying coaching as part of a degree or coaching qualification"--
Revised edition of Leadership team coaching in practice, [2018]
Includes bibliographical references and index.
Keywords: Teams in the workplace -- Management; Leadership; Employees -- Coaching of; Executive coaching